An Examination of University Student Workers' Motivations: A New Zealand Hospitality Industry Case Study. Issue 4 (1st October 2020) - Zhu, Dan; Kim, Peter Beomcheol; Poulston, Jill
ABSTRACT: A review of the extant hospitality literature reveals a paucity of research on student workers' motivations at work. Cognizant of the importance of international students to New Zealand hospitality organizations, this study, informed by Herzberg's motivation theory and using the IPA (Importance-Performance Analysis) model, examines international students' motivational factors in hospitality workplaces and investigates the relationships between their perceptions of motivational factors and their turnover intentions. A survey was conducted with 161 international students in Auckland, New Zealand. In contrast to Herzberg's theory, the findings reveal that good pay, work-life balance, and a comfortable working environment are the most important motivations for international students to work in hospitality. Besides, and consistent with Herzberg's theory, results also indicate that hygiene factors appear more effective than motivators in predicting turnover intentions. The discussion provides practitioners with insights into motivating and retaining student workers.